Different pendulum type dynamic vibration absorber aplication - Мартин, Віктор Євгенович; Дівеєв, Богдан Михайлович; Дорош, Ігор Романович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper considers the methods of calculation and optimization of different pendulum type dynamic vibration absorbers for the vibration reduction of elongated elements. Discrete-continuous models of the dynamics of oversize elongated elements based on the Timoshenko beam theory with attached discrete elements are presented. Algorithms for the vibration reduction of elongated machine elements are obtained. Noise and vibration are associated with many mechanical systems including industrial, household appliances, transportation machinery and buildings. Many of these structures are made up of beam type elements. Once the system parameters are defined, beam system vibration can be reduced using passive damping. The dynamic vibration absorber is effective, reliable and inexpensive device to reduce vibration, caused by harmonic or narrow-frequency disturbance. In the classical theory of dynamic vibration absorber, the primary structure is modeled by a mass-spring system, though other models also find interesting theoretical and engineering applications. In particular, pendulum type systems with a solid body at a fixed rotation point play an important role as a model in many branches of mechanical engineering, transport and construction. The application effect of the pendulum type dynamic vibration absorber with shock masses may significantly differ from using the mass-on-a spring system. Research and optimization of different type dynamic vibration absorbers are performed. Timoshenko beam with different clamping conditions and different type dynamic vibration absorbers are used as a model for many real systems, described in the literature. Methods of decomposition and numerical synthesis are considered based on the adaptive schemes. Structures of elongated elements of machines and buildings with regard to their interaction with the system of dynamic vibration absorbers are examined. The optimization method of dynamic vibration absorbers to reduce excessive vibration of the Timoshenko beam system under harmonic and shock perturbations is developed.